X-Y translocation in a retarded phenotypic male. Clinical, cytogenetic, biochemical, and serogenetic studies. Issue 6 (December 1978) - Bernstein, R; Wagner, J; Isdale, J; Nurse, G T; Lane, A B; Jenkins, T
Abstract : Cytogenetic studies on a mentally retarded boy revealed an X-Y translocation, karyotype 46, X, t(X;Y)(p22;q11). Only 5 other such cases have been reported and these were all females. The unequivocal male phenotype suggested non-random inactivation of the normal maternally derived X chromosome, and that the non-inactivated X-Y translocation chromosome included the locus for male determination. Confirmation of this was provided by unassociated X and Y chromatin in interphase cells, as well as by reverse banding after BrdU incorporation and autoradiography of metaphase chromosomes. There was anomalous Xg blood group inheritance in the proband, indicating possible localisation of the Xg locus to the terminal portion of the X short arm. Linkage of Xg and a form of X-linked mental retardation is suggested. Close linkage of the Xg locus with the loci for alpha-galactosidase, phosphoglycerate kinase, G-6-PD, and MPS II was excluded.